PEMBELAJARAN STEAM PADA PEMBUATAN INSTALASI PENJERNIHAN AIR MENGGUNAKAN BOTOL PLASTIK AIR MINERAL UNTUK MENGEMBANGKAN KREATIVITAS ANAK USIA DINI - Dewi Agustina; Roni Mugara; Rohmalina Rohmalina (IKIP Siliwangi, 2020)
The Learning of STEAM (Scientific Technology, Engineering, Art and Mathematics) is one of the innovations in Indonesian learning. STEAM learning can be applied at various levels of education. Early childhood needs a constructive stimulus in order to use mental operations and good logical thinking. Through the manufacture of water purification installation using plastic bottles of mineral water can develop a simple technology based psychomotor skills well. This simple Hastakarya requires the design of a tool that is in the description of work papers prepared by early childhood. In This phase, early childhood is trained to be able to take mathematically into the shape and size of the tool to make a simple design of precision and aesthetic look. This simple process of manufacturing aims to train children to develop basic scientific thinking that is at the heart of identifying problems, formulating questions, and collecting information and can draw conclusions and communicate them. STEAM learning is also aimed at making learning in PAUD take place fun and interactive. This is in accordance with with the philosophy of learning in the PAUD which is based on playing activities and interacting with the school environment. This data collection uses the method of literature using primary and secondary data sources then by analyzing the data, by reading the source books relating to the research and using a qualitative approach that seeks to describe or describe the learning activities that teachers do in class by researchers. The Final result of this study will be produced by a STEAM learning tool about the manufacture of simple water purification installations in PAUD and can activate the child's creativityPembelajaran STEAM (Scientific Technologi, Engineering, Art and Mathematics) merupakan salah satu inovasi pembelajaran di Indonesia. Pembelajaran STEAM diterapkan pada berbagai jenjang pendidikan. Anak usia dini membutuhkan stimulus agar dapat menggunakan operasi mental dan logika berpikir yang baik. Melalui pembuatan instalasi penjernihan air menggunakan botol plastik air mineral dapat mengembangkan teknologi sederhana berbasis keterampilan psikomotor. Hastakarya sederhana ini memerlukan rancang bangun alat yang terdeskripsi pada kertas kerja yang disusun anak usia dini. Pada fase ini, anak dilatih untuk dapat memperhitungkan secara matematis bentuk dan ukuran alat agar tampilan hastakarya terlihat presisi dan estetik. Proses pembuatannya bertujuan untuk melatih anak mengembangkan berpikir ilmiah dasar yang merupakan inti dari kemampuannya dalam mengumpulkan berbagai informasi. Pembelajaran STEAM juga bertujuan agar pembelajaran berlangsung menyenangkan dan interaktif. Hal ini sesuai filosofi pembelajaran di PAUD berdasar atas kegiatan bermain dan berinteraksi dengan lingkungan sekolah. Pengumpulan data ini menggunakan metode literature dengan menggunakan sumber data primer dan sekunder kemudian dengan menganalisis data, membaca buku sumber yang berkaitan dengan penelitian dan menggunakan pendekatan kualitatif yang berupaya mendeskripsikan kegiatan pembelajaran yang dilakukan guru di kelas oleh peneliti. Hasil akhir penelitian akan menghasilkan sebuah perangkat pembelajaran STEAM tentang pembuatan instalasi penjernihan air sederhana serta dapat mengaktivasi kreativitas anak.